Clinical Assessment for Lower Eyelid Blepharoplasty with Attention on Negative Prognostic Indicators - Vroegop, Anneclaire V.; Faris, Callum (Facial Plastic Surgery, 2023)
In the present report, a comprehensive approach on the assessment of the lower eyelid for blepharoplasty is provided. Important items such as anatomical key areas and surgical factors are discussed. Proper management of lower eyelid deformities requires an understanding of both intrinsic and extrinsic anatomical factors resulting in the unfavorable outcome.
Keywords: lower eye lid deformity; blepharoplasty; clinical eye lid assessment; complications